2005
DOI: 10.1186/1477-3155-3-9
|View full text |Cite
|
Sign up to set email alerts
|

Atomic force microscopy: a powerful tool for high-resolution imaging of spermatozoa

Abstract: Atomic force microscopy (AFM) has emerged as the only technique capable of real-time imaging of the surface of a living cell at nano-resolution. Since AFM provides the advantage of directly observing living biological cells in their native environment, this technique has found many applications in pharmacology, biotechnology, microbiology, structural and molecular biology, genetics and other biology-related fields. AFM has also proved to be a valuable tool for reproductive biologists. An exhaustive review on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 43 publications
0
8
0
1
Order By: Relevance
“…Assessment of the sperm cell by AFM provides topographic images, which can be viewed in 3D, allowing the observation of nanoscale details [15]. Moreover, AFM slides are prepared quickly and easily and under near-physiological conditions [25]. Although AFM imaging can be performed on living cells, a structural/temporal barrier prevents its use with live sperm cell due to the time spent to capture images from one single sample (∌10 min).…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of the sperm cell by AFM provides topographic images, which can be viewed in 3D, allowing the observation of nanoscale details [15]. Moreover, AFM slides are prepared quickly and easily and under near-physiological conditions [25]. Although AFM imaging can be performed on living cells, a structural/temporal barrier prevents its use with live sperm cell due to the time spent to capture images from one single sample (∌10 min).…”
Section: Discussionmentioning
confidence: 99%
“…For the characterization of sperm morphology, AFM has been demonstrated to be relevant to obtain highresolution 3D surface topography of fixed samples [21][22][23]. An AFM study of mammalian spermatozoa guided in understanding cell structure-function relationship, which is expected to have a significant application in human reproduction [24].…”
Section: Introductionmentioning
confidence: 99%
“…[20,21] As the only technique capable of real-time imaging of the surface of living cells in their native environment, this technique has found many applications in pharmacology, biotechnology, microbiology, structural and molecular biology, genetics and other biology-related fields. [22] Through AFM nanomechanical analysis, our laboratory has demonstrated that cell elasticity is highly correlated with metastatic potential; AFM nanomechanical profiling also has potential applications as a marker for cancer drug sensitivity. [23,24]…”
Section: Introductionmentioning
confidence: 99%